Idiopathic Spontaneous Intraperitoneal Hemorrhage Due to Vascular Malformations in the Muscularis of the Stomach: A Case Report - Zhou, Yuhang; Zhou, Yuchen; Li, Weihua; Lin, Shengtao (Frontiers in Medicine, 2022)
Idiopathic spontaneous intraperitoneal hemorrhage (ISIH) is a phenomenon caused by spontaneous rupture of intra-abdominal visceral vessels, and vascular malformations (VMs) leading ISIH is rare in previously reported cases. VMs of gastric wall which are commonly located in the mucosa and submucosa, mostly lead to upper gastrointestinal bleeding rather than intraperitoneal hemorrhage. To our knowledge, this is the first report of ISIH caused by VMs in gastric muscularis. In the current case, a 22-year-old male patient presented with sudden abdominal pain for 4 hours accompanied by tachycardia and hypotension. Computed Tomography (CT) revealed a hematoma in omental bursa and fluids in abdominopelvic cavities. Then intraperitoneal hemorrhage was confirmed after abdominal paracentesis. Furthermore, ultrasonic gastroscopy indicated that vascular malformation in the muscularis of the stomach probably led intraperitoneal hemorrhage. The patient recovered after conservative treatment based on fluid resuscitation and remained stable during 12 months follow-up. This case suggests that VMs located in gastrointestinal tract may lead to ISIH and ultrasonic gastroscopy is helpful in diagnosis of VMs in gastrointestinal tract.